Application of game-based learning in developing metacognition for facilitating English for specific purpose (ESP) vocabulary acquisition: A case study - Tan, Wilson (2023)
Insufficient vocabulary knowledge among business undergraduates often leads to problems in both written and spoken communication. Improving vocabulary is a conscious effort requiring metacognitive awareness, which refers to the ability of an individual to reflect, understand and control their learning. This study investigated the effect of game-based learning on ESP learners’ metacognitive awareness and vocabulary acquisition through a mixed-method approach. A total of 65 participants were involved in this study. The quantitative data were gathered through pre- and post-vocabulary tests and the adapted Metacognitive Awareness Inventory (MAI). The results showed there was a significant improvement in learners’ conditional knowledge and comprehension monitoring. Focus group interviews and a questionnaire were used to analyse the perception of the usefulness of game-based learning in developing metacognitive awareness and facilitating vocabulary acquisition. The findings from the qualitative data showed that game-based learning is effective in vocabulary acquisition as well as developing metacognitive awareness. These findings can help ESP practitioners, and course and syllabus designers incorporate game-based learning as a tool of learning to better allow students to learn the contents being taught.